The Effect of Light Exposure Duration on the Oxidative Stability and Sensory Profile of Avocado (Persea americana)-Based Mayonnaise - Dahlan, Sakinah Ahyani; Radjak, Maryam; Isra, Muhamad (PERTETA, 2025)
Avocado-based mayonnaise presents a novel formulation aimed at reducing the saturated fat content typically associated with conventional emulsified condiments. This investigation sought to delineate the impact of light exposure duration on the oxidative integrity and sensory parameters of mayonnaise derived from Persea americana. Employing a completely randomized design (CRD) comprising a single experimental factor—duration of light exposure (0, 24, 48, and 72 hours) each treatment was replicated thrice to ensure experimental reliability and statistical robustness. Analytical endpoints included moisture content, pH, peroxide value, free fatty acid (FFA) concentration, and sensory attributes (color and aroma). Statistical analyses involved ANOVA followed by Duncan’s Multiple Range Test at a 5% significance threshold. The results revealed that prolonged exposure led to a statistically significant decline in sensory acceptance (color score: 6.07 to 3.47; aroma score: 6.20 to 3.67) and elevated oxidative markers including moisture content, peroxide value, and FFA. Among the tested conditions, treatments L1 and L2 preserved compositional and sensory quality within permissible SNI standards for FFA (<3%). The study underscores the necessity of light-protective packaging in mitigating oxidative degradation in avocado-based emulsions and emphasizes the relevance of optimizing environmental exposure parameters during storage and distribution of lipid-rich food emulsions.